Síndrome cardiorrenal em pacientes idosos com insuficiência renal crônica leve a moderada - Gomes, Marcos Alvinair (2010)
Kidney dysfunction is a prevalent phenomenon in old age. In adults, kidney dysfunction is associated with an elevated risk of cardiac dysfunction and cardiovascular mortality. Left ventricular function in the elderly may be affected by the general decline in kidney disfunction with age. Evaluation of the blood creatinine level does not accurately reflect renal function in the elderly. Hypertension and metabolic disorders, which are frequently present in the elderly, may alter cardiac and kidney function. Most studies have suggested a link between chronic kidney disease and cardiac dysfunction in patients with a renal filtration rate under 45 ml/min/1.73 m2. Cardiac dysfunction may be present in elderly patients with a renal filtration rate between 45 and 90 ml/min/m2. Twenty-six men and twenty-two women aged sixty years or more were studied. Kidney function was evaluated by measuring the creatinine clearance rate, evaluating cardiac function by echocardiogram and establishing the metabolic profile by evaluating blood samples and a 24 hours collected urine.We evaluated each subject s history of coronary disease, hypertension, smoking status and cardiovascular drug profile. For statistical analysis, we used the Student s t Test and Linear Regression with significance set at p<0.05. Patients were separated into two groups: Group I included patients with normal kidney function (Creatinine Clearance ≥ 90 ml/min/1.73 m2) and Group II included those with early-stage kidney dysfunction (45 < Creatinine Clearance < 90 ml/min/1.73 m2). We found a significant difference in the ejection fraction between groups I and II (0.71±0,01 vs. 0.67±0,01 ; p<0.01), serum triglycerides (105.7±10 mg/dl vs. 143,3±16 mg/dl ; p=0.02), phosphate in 24 h urine (810.2±56 vs. 573,6±46 mg/dl ; p=0.002),calcium in 24 h urine (177,5± 33 vs. 107 ± 12 mg/dl ; p=0,03). Linear Regression analysis of Creatinine Clearance and the ejection fraction shows a statistically significant positive relationship (r=0.41; p=0.0036). No difference were observed between the two groups in terms of age, sex, hypertension, pulse pressure, cardiovascular drug use, smoking status, coronary disease, blood hemoglobin, glycemia, sodium, potassium, calcium, phosphate, uric acid, C-reactive Protein, homocysteine, total or fractioned cholesterol , serum creatinine, 24-h urine protein, creatinine, calcium , uric acid, left ventricular mass, relative posterior left ventricular thickness, cardiac output, left ventricular end-systolic volume or left ventricular end-diastolic volume. Our results suggest that mild kidney dysfunction in the elderly coexists with reductions in the ejection fraction when Creatinine Clearance is between 45 and 90 ml/min/1.73 m2. This relationship is not related to the presence of hypertension, metabolic or inflammatory disease, anemia, smoking status, coronary disease or use of cardiovascular drugs. Cardiorenal Syndrome can be detected early in asymptomatic elderly patients with Creatinine Clearance above 45 ml/min/1.73 m2. Based upon our results, we were not able to differentiate between Type 2 and 4 Cardiorenal Syndrome. These results may facilitate early care of the patients following cardiac changes and may therefore reduce cardiac mortality in this population.